STUDY OF LIFE CYCLE ASSESSMENT AND IMPROVEMENT FOR REDUCING GREENHOUSE GAS EMISSIONS IN TEA SHOOT FIELD PRODUCTION - Rezamela Erdiansyah; R. Wulansari; M. K. Prayoga; I. Fitri; E. Pranoto; Rosmeika; A. Sulaswaty (Gunung Djati Conference Series, 2026)
Tea industry is a crucial agricultural sector in Indonesia, that both contributes to and absorbs greenhouse gas (GHG) emissions. However, limited information exists about GHG emission during these processes. Chemical fertilizers predicted contribute the most portion to GHG emissions in the field, while tea cultivation requires nitrogen in a dominant composition with the most readily available source coming from urea fertilizer. Therefore, the objectives of this study are to calculate the impact of Global Warming Potential (GWP) in tea shoot field production process and to explore methods for reducing GWP through demonstration plots through a combination of bio-organo-mineral fertilizer applications to reduce urea use. The study was conducted in Negarakanaan Tea Plantation (1.350 m asl), West Java Indonesia during 2023 to 2024. The assessment of the life cycle impacts in field activities calculated using the Cool Farm Tool (CFT) software. There was no significant difference in total fresh shoot production between Bio-Organo-mineral combine with 50% Urea (8,246 kg/0.48 ha) and conventional 100% chemical dose fertilizer (8,049 kg/0.48 ha), even Bio-organo-mineral demonstrated a greater improvement in shoot production, particularly during the productive phase of the tea plants (Pruned Years 2 and 3). The GHG’s Emission for Bio-organo-mineral were only 55.16 kg CO₂eq per tons compare to conventional plots 125.10 kg CO₂eq per tons and baseline cultivation 186.85 kg CO₂eq per tons. The Bio-organo-mineral treatment improved fertilizer efficiency around 35.98% by reducing the urea dosage by 57.71% and reduced total GHG emissions (CO₂eq) by 55.90% compared to conventional plots.